2018
DOI: 10.1021/acsami.8b10170
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement in Low-Temperature-Processed Perovskite Solar Cells by Molecular Engineering of Porphyrin-Based Hole Transport Materials

Abstract: Porphyrin derivatives have recently emerged as hole transport layers (HTLs) because of their electron-rich characteristics. Although several successes with porphyrin-based HTLs have been recently reported, achieving excellent solar cell performance, the chances to improve this further by molecular engineering are still open. In this work, Zn porphyrin (PZn)-based HTLs were developed by conjugating fluorinated triphenylamine (FTPA) wings at the perimeter of the PZn core for low-temperature perovskite solar cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Azmi et al reported Zn porphyrin-based HTMs with conjugating fluorinated triphenylamine wings. The best among the series P Zn -2FTPA exhibited a PCE of 18.85% 139. Chiang et al designed and synthesized the dimeric porphyrin material WT3 with a suitable HOMO level and hole mobility leading to an excellent PCE of 19.44% 140.…”
Section: Introductionmentioning
confidence: 99%
“…Azmi et al reported Zn porphyrin-based HTMs with conjugating fluorinated triphenylamine wings. The best among the series P Zn -2FTPA exhibited a PCE of 18.85% 139. Chiang et al designed and synthesized the dimeric porphyrin material WT3 with a suitable HOMO level and hole mobility leading to an excellent PCE of 19.44% 140.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins are widely present in biological systems and have shown impressive performance for many optoelectronic applications, such as organic light-emitting diodes, hole-transporting materials for perovskite solar cells, sensitizers for photodynamic therapy, and DSSCs. 8–14…”
Section: Introductionmentioning
confidence: 99%
“…Azmi et al synthesized three types of zinc porphyrins bearing triphenylamino groups (7)(8)(9) to investigate the effect of introducing uorine, an electrophilic group, on the porphyrin substituents with the aim of improving electrochemical properties and device performance. 48 The HOMO levels by CV measurement were À5.14 eV for 7, À5.37 eV for 8, and À5.24 eV for 9. Introducing more uorine atoms or positioning a uorine atom close to the porphyrin core lowered the HOMO level.…”
Section: Porphyrins As Hole-transport Materials In Perovskite Solar Cmentioning
confidence: 92%